2014
DOI: 10.1038/npp.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Poverty and Stress Reactivity Are Associated with Aberrant Functional Connectivity in Default Mode Network

Abstract: Convergent research suggests that childhood poverty is associated with perturbation in the stress response system. This might extend to aberrations in the connectivity of large-scale brain networks, which subserve key cognitive and emotional functions. Resting-state brain activity was measured in adults with a documented history of childhood poverty (n ¼ 26) and matched controls from middle-income families (n ¼ 26). Participants also underwent a standard laboratory social stress test and provided saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 48 publications
5
119
1
2
Order By: Relevance
“…For example, Philip et al found that early life stress, in the absence of psychiatric illness and medication, was related to decreased connectivity between the PCC seed and mPFC [8]. Another study indicated that, in healthy adults, childhood poverty reduced PCC to vmPFC connectivity as compared to adults raised in middle-income households [27]. Further investigation of chronic stress, including early life stress, on the DMN will do much to enrich our understanding of changes to large-scale intrinsic connectivity networks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Philip et al found that early life stress, in the absence of psychiatric illness and medication, was related to decreased connectivity between the PCC seed and mPFC [8]. Another study indicated that, in healthy adults, childhood poverty reduced PCC to vmPFC connectivity as compared to adults raised in middle-income households [27]. Further investigation of chronic stress, including early life stress, on the DMN will do much to enrich our understanding of changes to large-scale intrinsic connectivity networks.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of inflammatory markers also mediated the associations between SED and white matter structure integrity in adulthood (Gianaros et al 2013). Childhood poverty exposure prospectively predicted weaker default mode network activity, which was associated with higher levels of cortisol in response to social stress (Sripada et al 2014).…”
Section: Multilevel Neurobiologyenvironment Interactionsmentioning
confidence: 95%
“…Premorbid vulnerability, such as early life stress, can alter receptor sensitivities within the HPA axis and blunt cortisol reactivity (Carpenter et al, 2007). Furthermore, prolonged early life stress such as growing up in poverty reduces hippocampal-prefrontal connections that alter hippocampal cortisol receptor sensitivities that shape adult cortisol levels and learning processes involving the hippocampus (Sripada et al, 2014). Several fMRI studies have shown that stressful stimuli can modulate neurocircuit function; for example, a study investigating the functioning of certain brain regions after inducing social stress found a decrease in amygdala-hippocampal connectivity that was associated with elevated salivary cortisol (Vaisvaser et al, 2013; Veer et al, 2012).…”
Section: The Maladaptive Feedback Loop Leading To Altered Brain Stmentioning
confidence: 99%